O impacto da complexidade tributária e dos parcelamentos especiais na tomada de decisão da (des)obediência tributária das empresas brasileiras listadas na B3: um estudo sob a ótica da teoria dos jogos - Antônio Paulo Machado Gomes (2020)
Since 2000, successive special installment plans have been published granting reductions in fines and interest rates to delinquent taxpayers in Brazil, a country well known for its tax complexity. In view of this fact, the general objective of this research study was to analyze the impact of the tax complexity and of the special installment plans on the decision of the companies listed in B3 not to comply with the Brazilian tax legislation. A panel logit model was used, estimating the likelihood of a company being noncompliant based on the independent variables of tax complexity, special installment plans, the interaction between these two variables, the likelihood of inspection, the punishment by the Selic rate, the inspections costs, and the expected usefulness. And as control variables, the current ratio, the ebitda, and the size of the company. The tax complexity variable was measured by the number of characters without spaces of the tax legislation related to the taxes studied. In addition, the number of laws was considered, as well as their amendments, to form the proxy of tax complexity in the model proposed. The installment plan variable, on the other hand, was identified by the number of adhesions to the special installment plans published between 2010 and 2018. The results of the logit model proposed confirmed the research hypotheses that the complexity and the special installment plans positively affect the likelihood of a company in making the decision to disobey. According to the research findings, the addition of 20 characters in the tax legislation causes an increase of 0.025 in the likelihood of that company adopting the strategy of disobedience. This way, the publication of a law with 1,000 characters increases by 25% the likelihood of a company being noncompliant. Regarding the special installment plans, it was identified that when they exist, the chances of a company adopting the strategy of tax disobedience increase twofold. And, for the interaction between the tax complexity and the special installment plans, this chance increases threefold. In addition, the findings have demonstrated that the low likelihood of inspection, as well as the high costs of inspection and the need for cash positively affect the likelihood of tax disobedience in the companies analyzed. And that the cost incurred by the increases in the Selic rate inhibit the tax disobedience. However, a decrease in the Selic rate increases disobedience by 1.08% in relation to tax disobedience. That is, increases in the Selic rate decrease the likelihood of disobedience, while decreases in the Selic rate mean even higher increases in the likelihood of disobedience.